PENERAPAN KOMPETENSI APARATUR DALAM PELAYANAN PUBLIK DI KECAMATAN ENTIKONG, KABUPATEN SANGGAU - AYU WIDOWATI JOHANNES (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2019)
This study aims to examine the application of competencies in the entikong sub-district apparatus in public services. this research uses descriptive qualitative method by conducting interviews, observation and documentation on regulations relating to apparatus competencies. the results of the study show that the entikong sub-district apparatus is required to have better competence and master the competence of public services. Apparatus who occupy positions in the Regional Apparatus must fulfill the requirements of technical, managerial and socio-cultural competence as well. government competency, so as to create adequate support of personnel both in the number and standard of competencies needed to carry out their duties and functions professionally, effectively and efficiently.